Communities of Difference
XXI, 231 p.
Keywords: This book will look at the implications of educational practices in communities that are differentiated by issues of language, culture, and technology. Trifonas argues that a 'community' is at once a gathering of like-minded individuals in solidarity of purpose and conviction, and also a gathering that excludes others. The chapters in this collection will reveal this tension between theory and practice in order to engage the models of community and the theories of difference that support them as a way to teach, to learn, and to know.